From Wolf-Hirschhorn syndrome to NSD2 haploinsufficiency: a shifting paradigm through the description of a new case and a review of the literature - Luisa Cortellazzo Wiel; Irene Bruno; Egidio Barbi; Fabio Sirchia (BMC, 2022)
Abstract Background Wolf-Hirschhorn syndrome (WHS) is a well-defined disorder, whose core phenotype encompasses growth restriction, facial gestalt, intellectual disability and seizures. Nevertheless, great phenotypic variability exists due to the variable extent of the responsible 4p deletion. In addition, exome sequencing analyses, recently identified two genes, namely NSD2 and NELFA, whose loss-of-function variants contribute to a clinical spectrum consistent with atypical or partial WHS. The observation of patients exhibiting clinical features resembling WHS, with only mild developmental delay and without the typical dysmorphic features, carrying microdeletions sparing NSD2, has lead to the hypothesis that NSD2 is responsible for the intellectual disability and the facial gestalt of WHS. While presenting some of the typical findings of WHS (intellectual disability, facial gestalt, microcephaly, growth restriction and congenital heart defects), NSD2-deleted children tend to display a milder spectrum of skeletal abnormalities, usually consisting of clinodactyly, and do not exhibit seizures. We describe the clinical picture of a child with WHS due to a de novo mutation of NSD2 and discuss the clinical and diagnostic implications. Case presentation A 6-year-old boy was evaluated for a history of intrauterine growth restriction, low birth weight, neonatal hypotonia, and psychomotor delay. No episodes of seizure were reported. At physical examination, he displayed marphanoid habitus, muscle hypotrophy and facial dysmorphisms consisting in high frontal hairline, upslanting palpebral fissures and full lips with bifid ugula. Cryptorchidism, shawl scrotum, mild clinodactyly of the right little finger and bilateral syndactyly of the II and III toes with sandal gap were also noted. The radiographic essay demonstrated delayed bone age and echocardiography showed mild mitral prolapse. Whole genome sequencing analysis revealed a heterozygous de novo variant of NSD2 (c.2523delG). Conclusions Full WHS phenotype likely arises from the cumulative effect of the combined haploinsufficiency of several causative genes mapping within the 4p16.3 region, as a contiguous genes syndrome, with slightly different phenotypes depending on the specific genes involved in the deletion. When evaluating children with pictures resembling WHS, in absence of seizures, clinicians should consider this differential diagnosis.